(untitled) (Journal of Applied Juvenile Justice Services, 2021)
The purpose of this paper was to explore the individual factors, job perceptions, and organizational characteristics that predict rehabilitation and punishment orientations among juvenile detention and probation staff members. Our results indicated juvenile officers who reported more education, less job ambiguity, and more adequate safety training were more likely to indicate preference for a rehabilitation orientation. However, those who reported less education, worked in detention rather than probation, and had higher job ambiguity were more likely to hold a punishment orientation. Finally, individual characteristics had a greater impact on both rehabilitation and punishment than either job perceptions or organizational factors. These results provide useful information for agencies about staff perceptions, which may in turn impact their interactions with and decision-making related to juvenile offenders under their supervision.